Three books on Bessarabia (Confluenţe Bibliologice, 2023)
The article presents the analysis of three books on the history of Bessarabia written by Nicolae Iorga in the work „The Romanian Nation from Bessarabia": I. H. Zucker „Bessarabia. Observations and reflections", I. G. Kolh, „Reisen in Sudrussland" and Dumitru C. Moruzzi, „ Bessarabia and its past (1712-1905)".
Keywords: history of Bessarabia; Romanian language